Is Repeated Arthrocentesis Beneficial in the Treatment of Temporomandibular Disorders: A Retrospective Study - Kutuk, Nükhet; KÜTÜK, NÜKHET; Bas, Burcu; Kazan, Dilara; Yuceer, Ezgi (My University, 2019)
Purpose: Arthrocentesis is an effective, simple, and minimally invasive treatment in patients with temporomandibular joint (TMJ) closed lock (CL). The aim of this study was to compare the effectiveness of 1- versus 2-session arthrocentesis procedures in the management of TMJ CL.